A new genus of Pharaxonothinae from Australia (Coleoptera: Erotylidae) - Yoshida, Takahiro; Leschen, Richard A.b. (Zootaxa, 2020)
Australonotha gen. nov. (type species: A. monteithi sp. nov.) is described for two specimens collected from Mount Bellender Ker, Queensland, Australia. Apart from having a monocondylic meso-metaventrital articulation, Australonotha shows similarities with other erotylid subfamilies including Dacninae, Cryptophilinae and some smaller bodied glabrous Languriinae. Australonotha is placed in Pharaxonothinae based on the presence of a transverse occipital ridge and absence of abdominal calli. It can be distinguished from members of all other erotylid taxa by the pronotum lacking a basal transverse groove and having a pair of submedial longitudinal pronotal grooves that are deep and widened posteriorly, have sharp edges laterad, and form part of a distinct rectilinear impression in the basal third.